Efektivitas Terapi Reminiscence terhadap Penurunan Tingkat Depresi pada Lansia: Literatur review - Yahya Firdaus Irawan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Depression is a common psychological problem experienced by the elderly and often arises due to physical changes, social limitations, and medical conditions that accompany the aging process. This disorder reflects uncomfortable emotional experiences. This study aims to review the effectiveness of reminiscence therapy in reducing depressive symptoms in the elderly through a literature review approach. The method used was a literature review by examining five indexed scientific articles retrieved from the PubMed, Wiley, and Frontiers databases, published within the last five years. The results indicate that reminiscence therapy can reduce levels of depression and anxiety, increase cognitive capacity, strengthen self-esteem, and support the quality of life of the elderly through the activity of remembering and sharing meaningful experiences. Overall, this review demonstrates that reminiscence therapy is an effective and holistic non-pharmacological approach to improving the mental health of the elderly.